2023
DOI: 10.3389/fcell.2023.1161778
|View full text |Cite
|
Sign up to set email alerts
|

The predictive effect of immune therapy and chemotherapy under T cell-related gene prognostic index for Gastric cancer

Abstract: Background: Gastric cancer (GC) is one of the most common malignancies in the human digestive tract. CD4+T cells can eliminate tumor cells directly through the mechanism of cytolysis, they can also indirectly attack tumor cells by regulating the tumor TME. A prognostic model of CD4+T cells is urgently needed to improve treatment strategies and explore the specifics of this interaction between CD4+T cells and gastric cancer cells. Methods: The detailed data of GC samples were downloaded from the Cancer Genome A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that abundant immune cells are infiltrated in the tumor microenvironment of GC, and the number and phenotype of immune cell subpopulations in GC tissues are closely correlated with the development and prognosis of GC patients [ 35 ]. CD4 T cells are a special type of T cells targeting tumor cells in various ways, which can directly eliminate tumor cells through cytolysis, or indirectly kill tumor cells by increasing the number of B Cells and CTL (Cytotoxic T Lymphocytes) responses [ 36 , 37 ]. Existing study reveals that DNA damage repair and immunogenic tumor microenvironment in GC could be characterized by activated subsets of CD4 T cells [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that abundant immune cells are infiltrated in the tumor microenvironment of GC, and the number and phenotype of immune cell subpopulations in GC tissues are closely correlated with the development and prognosis of GC patients [ 35 ]. CD4 T cells are a special type of T cells targeting tumor cells in various ways, which can directly eliminate tumor cells through cytolysis, or indirectly kill tumor cells by increasing the number of B Cells and CTL (Cytotoxic T Lymphocytes) responses [ 36 , 37 ]. Existing study reveals that DNA damage repair and immunogenic tumor microenvironment in GC could be characterized by activated subsets of CD4 T cells [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The progression of renal clear cell carcinoma (RCCC) is intricately linked to the immune system, with a particular emphasis on the distribution and function of T cells within the tumour microenvironment, exerting a direct influence on RCCC's growth and dissemination. 9 , 10 , 11 However, the heterogeneity within these T‐cell populations remains a subject warranting more comprehensive exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Glypican-3 expression in cancer-associated fibroblasts is a critical prognostic biomarker for PD-1 blockage therapy in GC ( Li et al, 2023 ). The T-cell-related gene prognostic index is a potential prognostic indicator used to distinguish the response to immune checkpoint inhibitor (ICI) therapy ( Chen J. et al, 2023 ). The neutrophil-to-lymphocyte ratio is an effective biomarker used for evaluating the prognosis of GC patients who received ICI therapy ( Li and Pan, 2023 ).…”
Section: Introductionmentioning
confidence: 99%